2001
DOI: 10.1161/hs0901.094623
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Disorder, Dysthymia, and Risk of Stroke

Abstract: Background and Purpose-This study examined depressive disorder as a risk factor for incident stroke in a prospective, population-based design. Methods-The Baltimore Epidemiologic Catchment Area Study is a prospective 13-year follow-up of a probability sample of household residents from Baltimore, Md. Depressive disorder was measured with the diagnostic interview schedule, and stroke was assessed by questions from the health interview survey or by documentation on a death certificate. Results-During the 13-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
1
8

Year Published

2002
2002
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(77 citation statements)
references
References 27 publications
4
64
1
8
Order By: Relevance
“…We speculate whether this indicates that prior depression might be a risk factor for stroke, a finding reported in a number of studies. [15][16][17] It is, however, still unknown whether depression before a clinical stroke is an independent stroke risk factor or a consequence of silent strokes. 18 The antiplatelet effect of SSRIs may occur only during treatment with high doses or after long-term exposure to SSRIs.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate whether this indicates that prior depression might be a risk factor for stroke, a finding reported in a number of studies. [15][16][17] It is, however, still unknown whether depression before a clinical stroke is an independent stroke risk factor or a consequence of silent strokes. 18 The antiplatelet effect of SSRIs may occur only during treatment with high doses or after long-term exposure to SSRIs.…”
Section: Discussionmentioning
confidence: 99%
“…9 Moreover, large-scale studies revealed an association between mood disorders and susceptibility to stroke. [10][11][12] However, although numerous theories have been proposed to explain the amplified risk of cardiovascular disease in patients with depression (reviewed by Everson-Rose and Lewis, 3 Lett et al 9 and Holtzheimer and Nemeroff 13 ), the exact biological mechanisms by which depression may increase the risk of cardiovascular events have not been completely elucidated so far.…”
Section: Introductionmentioning
confidence: 99%
“…While they are often considered to be a complication of these neurologic disorders, epidemiologic studies published in the last 15 years have suggested a bidirectional relation. Indeed, not only are these neurologic conditions associated with an increased risk of DD, but a history of depression has been associated with a four-to seven-fold higher risk of developing epilepsy (1) and a two-to three-fold higher risk of having a stroke, Parkinson's disease, or dementia (2)(3)(4). This bidirectional relation does not imply causality but reflects most likely the presence of common pathogenic mechanisms operant in DD and these neurologic disorders.…”
Section: Commentarymentioning
confidence: 99%